2014
DOI: 10.1002/jsfa.6963
|View full text |Cite
|
Sign up to set email alerts
|

A correlation between tocopherol content and antioxidant activity in seeds and germinating seeds of soybean cultivars

Abstract: Total tocopherol content was higher in soybean landraces as compared with modern cultivars developed by cross-breeding. These results suggest that soybean breeding is necessary to increase tocopherol levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…It is plausible to conclude that this delay in quantifying the tocopherol levels would lead to lower and/or unpredictable levels, as past results suggested that soybean seed storage caused major tocopherol losses (Wohleser, 2007). Degradation of tocopherols during seed storage reported in another study, however, found that tocopherol levels and ratios remain consistent for up to 6 mo of storage (Lee et al, 2015). The 2010 soybean seeds were subjected to HPLC analysis immediately after harvest in November and December of 2010.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is plausible to conclude that this delay in quantifying the tocopherol levels would lead to lower and/or unpredictable levels, as past results suggested that soybean seed storage caused major tocopherol losses (Wohleser, 2007). Degradation of tocopherols during seed storage reported in another study, however, found that tocopherol levels and ratios remain consistent for up to 6 mo of storage (Lee et al, 2015). The 2010 soybean seeds were subjected to HPLC analysis immediately after harvest in November and December of 2010.…”
Section: Discussionmentioning
confidence: 98%
“…Soybean seed contains high levels of tocopherols, which in their natural form provide benefits against many human health conditions such as lung cancer, chronic inflammation, and cardiovascular disease. The benefits can be attributed to the tocopherols' strong antioxidative properties, which protect cells from reactive oxygen species and also help by impacting cellular responses to oxidative stress (Lee et al, 2015). The main purpose of tocopherols in soybean seed is to protect the lipids from lipid peroxidation (Evans et al, 2002).Agronomic practices and location and year effects on tocopherols are very important in understanding the influence that they have in causing tocopherol profile differences.…”
mentioning
confidence: 99%
“…Tocopherols and carotenoids are well known for their antioxidant functions in prevention of various chronic diseases (Agarwal & Rao, 2000; Valentin & Qi, 2005). We believe that these fat‐soluble micronutrients in Cheongja#3 create a synergistic effect with the antioxidant functions of black soybeans in Cheongja#3 soybean extract than that is not found in other soybean varieties (Lee, Park, et al., 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Their biological activities including antioxidative and anti-inflammatory effects help to reduce the risk of cancer and metabolic disorders (Ganesan & Xu, 2017). Cheongja#3 is a cultivar of black soybean which is well known to contain high amounts of anthocyanins as well as tocopherols (Lee et al, 2009;Lee, Park, et al, 2015). Several previous studies have shown that Cheongja#3 had antiobesity effects in cells, mice, and humans (Jeon, Lee, & Cheon, 2015;Kim et al, 2015;Lee, Sorn, Park, & Park, 2016), as well as neuroprotective effects (Bhuiyan, Kim, Ha, Kim, & Cho, 2012;Kim, Chung, et al, 2012).…”
mentioning
confidence: 99%
“…Then, we identified lutein (111.8 μg/100 g), γ-tocotrienol (757.7 μg/100 g) and γ-tocopherol (4071.4 μg/100 g) in SBx. These bioactive components are well known antioxidant components, thus leading to various biological functions for health benefits [ 36 , 37 ]. Further studies are necessary with regard to determination of functional groups or their purity in these extracts to understand the mechanism of actions for their antioxidant activities.…”
Section: Resultsmentioning
confidence: 99%